Social And Environmental Dynamics In Economic Resilience: A Review Of The Influence On GRDP - Kendani, Sherin Shifa; Febriani, Ratu Eva (Universitas Bengkulu, 2024)
Abstract This study analyzes the influence of social and environmental dynamics on economic resilience, which is measured through Gross Regional Domestic Product (GRDP) on the island of Sumatra during the period 2011 to 2022. Considering the increasing uncertainty in the global economy due to climate change, this research aims to analyze how factors such as Poverty level, unemployment rate, Human Development Index (HDI), air quality index, water quality index and environmental quality index affect GRDP. Using a quantitative approach, secondary data from ten provinces in Sumatra during the period 2011 to 2022 was analyzed using the panel data regression method. The findings show that poverty has a significant negative effect on GRDP, while HDI has a positive effect on GRDP. In addition, air and water quality indices have a negative impact on GRDP, highlighting the need for effective environmental management strategies. This research underscores the important relationship between environmental conditions and economic performance, showing that sustainable development strategies are critical to increasing economic resilience in vulnerable regions such as Sumatra. Keywords:Social and Environmental Dynamics, Economic Resilience, GRDP, Poverty, Environmental Quality Abstrak Penelitian ini menganalisis pengaruh dinamika sosial dan lingkungan terhadap ketahanan ekonomi yang diukur melalui Produk Domestik Regional Bruto (PDRB) di Pulau Sumatera selama periode 2011 hingga 2022. Mengingat meningkatnya ketidakpastian dalam perekonomian global akibat perubahan iklim, penelitian ini bertujuan untuk menganalisis bagaimana faktor-faktor seperti tingkat kemiskinan, tingkat pengangguran, Indeks Pembangunan Manusia (IPM), indeks kualitas udara, indeks kualitas air, dan indeks kualitas lingkungan mempengaruhi PDRB. Dengan menggunakan pendekatan kuantitatif, data sekunder dari sepuluh provinsi di Sumatera selama periode 2011 hingga 2022 dianalisis dengan menggunakan metode regresi data panel. Hasil penelitian menunjukkan bahwa kemiskinan berpengaruh negatif signifikan terhadap PDRB, sedangkan IPM berpengaruh positif terhadap PDRB. Selain itu, indeks kualitas udara dan air memiliki dampak negatif terhadap PDRB, menyoroti perlunya strategi pengelolaan lingkungan yang efektif. Penelitian ini menggarisbawahi hubungan penting antara kondisi lingkungan dan kinerja ekonomi, yang menunjukkan bahwa strategi pembangunan berkelanjutan sangat penting untuk meningkatkan ketahanan ekonomi di daerah yang rentan seperti Sumatera. Kata kunci : Dinamika Sosial dan Lingkungan, Ketahanan Ekonomi, PDRB, Kemiskinan, Kualitas Lingkungan